BEYOND TECHNICAL SKILLS: POSITIVE BEHAVIOR SUPPORT AS A FOUNDATION FOR AI-ERA COMPETENCIES IN ELEMENTARY TEACHER EDUCATION - Muhammad Arief Budiman; Anggun Dwi Setya Putri; Risma Septiana; Senopati Mahesa Bhirawa; Shafira Melinda Sundus; Syams Aris Ibrahim; Thesalonica Nur Ayua Rensi (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
AI integration demands ethical competence and emotional regulation in students, yet the preparation of PGSD teachers within the Positive Behavior Support (PBS) framework remains very limited. This study aims to analyze PBS as a supportive learning environment framework aligned with the Merdeka Curriculum and the Pancasila Student Profile. Using a mixed-methods design with 182 elementary school teachers and PGSD students, the research phase included a quantitative survey and in-depth semi-structured interviews. Statistical findings indicate that respondents' PBS knowledge level had a high average score of 4.08. Through structural model analysis, it was demonstrated that PBS knowledge significantly predicted classroom management practices (β = 0.58), which in turn influenced character alignment (β = 0.54) and teaching competency in the AI ​​era (β = 0.49). There was an indirect effect through the curriculum alignment variable of 0.22. Qualitative findings confirmed that PBS strengthens human-centered pedagogy, encourages responsible use of technology, and optimizes the formation of religious and independent character. The main conclusion of the study establishes PBS as the foundation for future teacher professionalism for the sustainability of inclusive national education reform. The integration of PBS into the PGSD curriculum is urgently needed to produce professional educators who are responsive to students' social-emotional needs while simultaneously guiding technological transformation throughout Indonesia in a sustainable, humanistic manner.